Cross-validation of a high-performance liquid chromatography nevirapine plasma assay in a resource-limited setting in Zimbabwe - Faithful Makita-Chingombe; Anthony T. Podany; Timothy Mykris; Farai Muzambi; Richard W. Browne; Andrew J. Ocque; Robin DiFrancesco; Lee C. Winchester; Courtney V. Fletcher; Tinashe Mudzviti; Charles C. Maponga; Gene D. Morse (AOSIS, 2021)
An international HIV pharmacology specialty laboratory (PSL) was established at the University of Zimbabwe to increase bioanalytical and investigator capacities. Quantitation of plasma nevirapine in samples from the AIDS Clinical Trials Group protocol 5279 was compared between the University of Nebraska Medical Center PSL and the University of Zimbabwe PSL. Both PSLs employed internally developed methods utilising reverse-phase high-performance liquid chromatography with ultraviolet detection. Eighty-seven percent of the cross-validation results exhibited ± 20% difference.